Learning and student satisfaction in postgraduate virtual scenarios 2010-2014-2015 - Ana María de Guadalupe Arras Vota; María del Carmen Gutiérrez Diez; José Luis Bordas Beltrán (Universidad de Guadalajara, 2017)
One of the existing signs in the history of mankind in the electronic union of the planet, which manifests itself by the presence of ICT in all spheres of human endeavor, including education, this has generated new paradigms that demand technological updating, teacher training and analysis of the processes in educational institutions. Hence the importance of carrying out this research, from a case study, with the purpose to analyze, learning scenarios and satisfaction of virtual learning mode graduate students of the Autonomous University of Chihuahua in three periods: 2010, 2014 y 2015. Methods used were analytical-synthetic and theoretical-deductive. The techniques were bibliographic, survey, and structured interview. Results reflect a tendency to individual work and the need to incorporate a more creative aspect in the tasks that teachers ask for, also, it reveals the need of more interaction between involved actors in the process, more teachers' commitment in tutorial work and in digital alphabetization, as well as the need to stimulate collaborative work and connective learning between students. All this to attain more quality in virtual education.